Formation of 5α-dihydrotestosterone from 5α-androstane-3α, 17β-diol in prostate cancer LAPC-4 cells – Identifying inhibitors of non-classical pathways producing the most potent androgen. Issue 2 (15th January 2020) - Boutin, Sophie; Roy, Jenny; Maltais, René; Poirier, Donald
Graphical abstract: Highlights: [ 14 C]-5α-androstane-3β, 17β-diol (3α-diol) was synthesized from [ 14 C]-testosterone. A biological assay was developed to measure the oxidation of [ 14 C]-3α-diol in cells. Inhibitors of dihydrotestosterone (DHT) formation from 3α-diol were identified. DHT formation via non-classic pathways was inhibited in prostate cancer LAPC-4 cells. Abstract: 5α-Dihydrotestosterone (5α-DHT) possesses a great affinity for the androgen receptor (AR), and its binding to AR promotes the proliferation of prostate cancer (PC) cells in androgen-dependent PC. Primarily synthesized from testosterone (T) in testis, 5α-DHT could also be produced from 5α-androstane-3α, 17β-diol (3α-diol), an almost inactive androgen, following non-classical pathways. We reported the chemical synthesis of non-commercially available [4- 14 C]-3α-diol from [4- 14 C]-T, and the development of a biological assay to identify inhibitors of the 5α-DHT formation from radiolabeled 3α-diol in LAPC-4 cell PC model. We measured the inhibitory potency of 5α-androstane derivatives against the formation of 5α-DHT, and inhibition curves were obtained for the most potent compounds (IC50 = 1.2–14.1 μM). The most potent inhibitor 25 (IC50 = 1.2 μM) possesses a 4-(4-CF3 -3-CH3 O-benzyl)piperazinyl methyl side chain at C3β and 17β-OH/17α-CCH functionalities at C17 of a 5α-androstane core.